Dokumen Software Requirement Specification Sistem Informasi Akuntansi Biaya (Studi Kasus PT. ABC) - Yuvela Handriani; Soetam Rizky Wicaksono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research focuses on the design and development of a Software Requirements Specification (SRS) document for the Cost Accounting Information System at PT. ABC, a rubber manufacturing company in Indonesia. In an effort to enhance the company's efficiency and productivity, this SRS document is prepared based on the international standard ISO/IEC/IEEE 29148:2018, which covers essential aspects such as functional requirements, performance, usability, interfaces, and others. The large number of business processes carried out manually, especially in the scope of cost accounting, means that the absence of an integrated cost accounting information system is one of the main factors preventing PT. ABC from achieving optimal efficiency in its business processes. In the context of the manufacturing industry, cost accounting plays a crucial role in controlling production costs, overhead, raw materials, and indirect labor. The results of this research will produce several modules, including factory overhead cost transactions, raw material cost transactions, direct labor cost transactions, manufacturing goods transactions, finished goods transactions, purchase return transactions, sales transactions, component purchase transactions, component mastering, position mastering, user mastering, cost mastering, supplier mastering, employee mastering, raw material cost reports, factory overhead cost reports, direct labor cost reports, cost of goods sold reports, cost variance reports, budget cost reports, and profit and loss reports.